KAJIAN IMPLEMENTASI KEBIJAKAN ORGANISASI KESATUAN PENGELOLAAN HUTAN (KPH) DI DAERAH (STUDI KASUS KPH BANJAR, KALIMANTAN SELATAN DAN KPH LALAN MANGSANG MENDIS, SUMATERA SELATAN) - Elvida Yosefi Suryandari; Sylviani Sylviani (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2012)
Forest Management Units (FMUs) establishment has been laid as a strategic objective to better management of forests. However, problems are still encountered in the development of FMUs, such as institutional framework of its funding and human resources avaibility. This study aims to: (1) analyze the policy implementation of FMU organization; and (2) analyze the availability of human resources in FMU development. The study was conducted in Lalan Mangsang Mendis FMU, South Sumatra Province and Banjar FMU, South Kalimantan Province. The data were collected using purposive sampling and analyzed using human resource planning analysis and policy analysis. The results showed that the current form of FMU organization is a technical implementation unit of